Efficacy of lumbosacral and sacrococcygeal epidural ropivacaine in dogs undergoing surgery for perineal hernia - Salla, Kati; Åhlberg, Tuuli; Lepajoe, Jaan; Kallio-Kujala, Ira; Mölsä, Sari; Casoni, Daniela (Frontiers in Veterinary Science, 2023)
Epidural anaesthesia is commonly administered as part of balanced anaesthesia for perioperative analgesia. The main goal of this randomized clinical trial was to compare the efficacy of two epidural approaches in dogs undergoing surgery for a perineal hernia. A secondary aim was to compare motor blockade. Intact ASA 1 and 2 male dogs, weighing ≤ 25 kg with no previous surgery for perineal hernia were enrolled.After premedication with IM acepromazine 0.02 mg/kg and butorphanol 0.3 mg/kg, general anaesthesia was induced with propofol and maintained with sevoflurane in oxygen. Dogs were randomly allocated to receive either a lumbosacral (LS, n = 30) or a sacrococcygeal (SC, n = 26) epidural injection with ropivacaine 1% (0.2 mL/kg) under computed tomography guidance.Successful analgesia was defined as no need of intraoperative rescue analgesia (fentanyl 3 µg/kg IV). Clinical failure was defined as the need of more than two boluses of fentanyl/hour Each dog received meloxicam 0.2 mg/kg IV at the end of the surgery. The Glasgow Composite Pain Scale short form (GCPS-SF), tactile sensitivity, pressure pain thresholds and motor blockade were assessed at 4, 6, 8 and 24 hours after the epidural injection. Methadone (0.2 mg/kg, IV) was administered if the GCPS-SF was ≥ 6/24 points. Differences between groups were analysed with the Mann-Whitney U test, Student's t-test or Fisher's Exact test, as appropriate. Success rate was assessed for non-inferiority between groups. The non-inferiority margin was set at -10%.Epidural analgesia was successful in 24 dogs in group LS and 17 dogs in group SC (p = 0.243), resulting in success rates of 80% and 65% in LS and SC groups, respectively. The non-inferiority of group SC versus group LS was confirmed. Clinical failure was recorded in two dogs in group LS and one dog in group SC. No significant differences between groups were detected in the GCPS-SF score, tactile sensitivity, pressure pain thresholds, need of post-operative methadone, or motor blockade. Both epidural techniques are valuable analgesic options for perineal hernia repair in dogs.